In-situ polymerized PMMA / TPU-based dual-filler polymer gel electrolyte and its preparation method and application

PMMA/TPU-based dual filler polymer gel electrolyte was prepared at room temperature by in situ polymerization, and aluminum-doped lithium lanthanum zirconium oxygen and nanoelectrolite were used as inorganic fillers, which solved the problems of low ionic conductivity and poor mechanical properties of gel electrolyte at room temperature, achieving both high ionic conductivity and high mechanical properties, and is suitable for lithium metal batteries.

CN117154206BActive Publication Date: 2025-04-22HARBIN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310984381.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-04-22
Estimated Expiration
2043-08-07

AI Technical Summary

Technical Problem

The low ionic conductivity and poor mechanical properties of gel electrolytes at room temperature limit their application in lithium metal batteries.

Method used

In situ polymerization method, a toughened high ionic conductivity gel electrolyte was prepared using PMMA/TPU film as the matrix, aluminum-doped lithium lanthanum zirconium oxygen (LALZO) and nanoelectroite (HNT) as inorganic fillers.

Benefits of technology

At room temperature, the ionic conductivity of the gel electrolyte reaches 6.75×10-4S/cm, while improving mechanical properties, and is suitable for lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117154206B_ABST
    Figure CN117154206B_ABST
Patent Text Reader

Abstract

The present invention relates to an in-situ polymerized PMMA / TPU-based dual-filler polymer gel electrolyte and a preparation method and application thereof, belonging to the technical field of lithium ion batteries. The present invention aims to solve the technical problems of low ionic conductivity and low mechanical properties of gel electrolyte at room temperature. The method of the present invention comprises the following steps: adding methyl methacrylate (MMA), thermoplastic polyurethane (TPU), initiator, aluminum-doped lithium lanthanum zirconium oxide (LALZO), nano-halloysite (HNT), polycarbonate (PC) and lithium salt to a solvent, stirring magnetically until the mixture is uniform, and obtaining a mixed solution; placing the obtained mixed solution in a PTFE culture dish, polymerizing and treating at high temperature, and obtaining a polymer composite membrane; immersing the polymer composite membrane in an electrolyte, and obtaining a composite gel electrolyte membrane. The gel electrolyte membrane provided by the present invention has the characteristics of high mechanical properties and good anti-lithium dendrite effect, and the ionic conductivity of the gel electrolyte membrane can reach 6.75×10 ‑4 S / cm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical energy storage batteries, and specifically relates to an in-situ polymerized PMMA / TPU-based double-filler polymer gel electrolyte and a preparation method and application thereof. Background Art

[0002] Traditional liquid electrolytes have advantages such as high ionic conductivity and good interfacial compatibility, but their volatility, flammability and instability to lithium metal limit their application in high energy density batteries. Solid electrolytes can solve the problems of volatility, flammability and instability of lithium metal in liquid electrolytes. Inorganic solid electrolytes have the advantages of non-flammability, wide electrochemical stability window and high ionic conductivity, and solid polymer electrolytes have the advantages of high safety, high film forming ability and low cost. However, inorganic solid electrolytes have the problem of poor interfacial compatibility, and solid polymer electrolytes show poor ionic conductivity at room temperature, which seriously hinders practical applications.

[0003] Gel electrolyte, as an intermediate state between liquid electrolyte and solid electrolyte, is a semi-solid electrolyte mixed with liquid and solid, which reduces the production safety problems such as electrode corrosion and oxidation combustion caused by leakage of organic liquid electrolyte. Due to the high crystallinity of the polymer matrix itself, the chain segment movement is restricted at room temperature, which reduces the lithium ion transmission rate. In addition, the presence of liquid components in the gel electrolyte reduces the mechanical properties of the polymer itself. The addition of organic fillers can reduce the crystallinity of the polymer, but the reduction in crystallinity is often accompanied by weakening of mechanical properties. The addition of inorganic fillers can improve the mechanical properties of the polymer, but the uneven dispersion in the matrix can easily cause slow and uneven lithium ion transmission, inducing the growth of lithium dendrites. Therefore, it is urgent to prepare a gel electrolyte with both high ionic conductivity and high mechanical properties at room temperature. Summary of the invention

[0004] The present invention aims to solve the technical problems of low ionic conductivity and low mechanical properties of gel electrolytes at room temperature, and provides a toughened high ionic conductivity gel electrolyte with PMMA / TPU film as a matrix, aluminum-doped lithium lanthanum zirconium oxide (LALZO) and nano-halloysite (HNT) as inorganic fillers, a preparation method thereof, and application in lithium metal batteries.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] The object of the present invention is to provide a method for preparing an in-situ polymerized PMMA / TPU-based dual-filler polymer gel electrolyte, which is specifically carried out according to the following steps:

[0007] Step 1, adding methyl methacrylate (MMA) and thermoplastic polyurethane (TPU) to a solvent, stirring until the thermoplastic polyurethane (TPU) is dissolved, adding an initiator, stirring under a closed condition, heating in a water bath, and then adding aluminum-doped lithium lanthanum zirconium oxide (LALZO), HNT powder and PC mixed evenly, stirring under a closed condition until uniform; then adding lithium salt, stirring under a closed condition until the mixture is uniform, to obtain a mixed solution

[0008] Step 2, placing the mixed solution obtained in the above step 1 in a PTFE culture dish, polymerizing and treating at high temperature to obtain a polymer composite membrane; immersing the polymer composite membrane in an electrolyte to obtain a composite gel electrolyte membrane.

[0009] It is further defined that in step 1, the diameter of the aluminum-doped lithium lanthanum zirconium oxide (LALZO) powder is 300 nm.

[0010] It is further defined that in step 1, the initiator is azobisisobutyronitrile (AIBN) or dibenzoyl peroxide (BPO).

[0011] It is further defined that in step 1, the stirring is magnetic stirring, and the speed is controlled at 450r / min to 600r / min.

[0012] It is further defined that the magnetic stirring time after the initiator is added is 1 h to 2 h, and the water bath heating temperature is 55° C. to 65° C.

[0013] It is further defined that in step 1, the lithium salt can be any one of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluorophosphate (LiPF6), and lithium perchlorate.

[0014] It is further defined that in step 1, the mass ratio of methyl methacrylate to thermoplastic polyurethane is (3:2) to (4:1).

[0015] It is further defined that the solvent in step 1 is one of N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, acetone, or a mixture of any ratio of any of them, or a mixture of several of them.

[0016] It is further defined that the amount of solvent added is 10 to 30 times the mass of the polymer.

[0017] It is further defined that in step 1, the mass ratio of methyl methacrylate, thermoplastic polyurethane, initiator, LALZO, HNT, polycarbonate (PC) and lithium salt is 1:(0.5-1):(0.01-0.05):(0.1-1):(0.1-0.2):(0.1-0.2), and the amount of initiator used is 0.05% to 0.1% of the mass of the polymerized monomer.

[0018] It is further defined that the electrolyte in step 2 is a secondary electrolyte having a formula of 1.0 M LiPF6 at EC:DEC=1:1 Vol%.

[0019] It is further defined that the operation process of making the film in step 2 is: injecting the mixed solution into a PTFE culture dish, placing it in a forced air drying oven for prepolymerization; first forced air drying, then vacuum drying, and after cooling to room temperature, obtaining a polymer composite membrane.

[0020] It is further defined that in step 2, the temperature and time of the prepolymerization of the MMA monomer are 60° C. to 70° C. and 20 min to 30 min, respectively.

[0021] It is further defined that in step 2, the temperature and time of air drying are 50-60° C. and 5-7 h respectively.

[0022] It is further defined that in step 2, the temperature and time of vacuum drying are 50-60° C. and 24-28 h, respectively.

[0023] Further, in step 2, the injection amount of the in-situ polymerization gelation mixed solution is 0.15 g / cm 2 ~0.2g / cm 2 .

[0024] A PMMA composite gel electrolyte prepared by any of the above methods.

[0025] A gel electrolyte membrane prepared by any of the above methods or use of the above gel electrolyte membrane in a lithium metal battery.

[0026] Compared with the prior art, it has the following beneficial effects:

[0027] The present invention adopts an in-situ polymerization method, and adds methyl methacrylate (MMA), thermoplastic polyurethane (TPU), an initiator, an inorganic filler LALZO, HNT and a lithium salt into a solvent, and mixes and stirs them evenly to obtain a mixed solution. Among them, methyl methacrylate (MMA) is a reactive monomer, TPU is a continuous phase, and the inorganic filler LALZO, HNT and lithium salt are dispersed phases. Since TPU is a semi-crystalline polymer with good swelling properties, the monomer MMA is soluble in a single phase, and its polymer is insoluble in the entire system, so the polymerization reaction occurs in the dispersed phase, and the polymer formed by the polymerization reaction runs through the continuous phase to obtain a gel electrolyte membrane with a network structure.

[0028] The gel electrolyte membrane in the present invention is prepared by adding a plasticizer to a solid electrolyte, combining the advantages of high safety of solid electrolytes and high ionic conductivity of liquid electrolytes, solving the problems of poor mechanical properties of PMMA prepared by in-situ polymerization and low ionic conductivity of gel electrolytes at room temperature. At room temperature, when the mass fraction of LALZO in the polymer is 30% (calculated according to the total mass of PMMA and TPU), the ionic conductivity of the gel electrolyte membrane can reach 6.75×10 -4 S / cm.

[0029] In order to further understand the features and technical contents of the present invention, please refer to the following detailed description and drawings of the present invention. However, the attached drawings are only provided for reference and illustration and are not intended to limit the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the SEM image of the PMMA / TPU / HNT / 30% LALZO polymer film without electrolyte absorption;

[0031] Figure 2 Graph showing the ionic conductivity of PMMA / TPU / HNT / LALZO (0–40%) gel electrolyte membranes with different LALZO contents. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0034] Example 1: The preparation method of the in-situ polymerized PMMA / TPU / HNT / 10% LALZO gel electrolyte membrane in this example is achieved by the following steps:

[0035] 1. Weighing:

[0036] Weigh the following materials respectively: methyl methacrylate (MMA) 6 g, thermoplastic polyurethane (TPU) 4 g, lithium hexafluorophosphate (LiPF6) 1 g, N,N-dimethylformamide (DMF) 80 g, azobisisobutyronitrile (AIBN) 0.3 g, LALZO 1 g, HNT 0.2 g, PC 1 g;

[0037] 2. The operation process of preparing gel electrolyte is:

[0038] Step 1. Add methyl methacrylate (MMA) and thermoplastic polyurethane (TPU) to N,N-dimethylformamide (DMF), and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add initiator azobisisobutyronitrile (AIBN), heat in a water bath at 55°C and magnetically stir at a speed of 500 r / min for 1 hour under closed conditions to obtain a mixed solution A; add evenly mixed LALZO, HNT powder and PC to the mixed solution A, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add lithium salt, and magnetically stir at a speed of 500 r / min for 1 hour under room temperature and closed conditions to obtain a mixed solution B.

[0039] Step 2. Inject the mixed solution B obtained in the previous step into a PTFE culture dish, place it in a forced air drying oven, and prepolymerize it at 70°C for 20 minutes; after prepolymerization, blow dry it at 60°C for 5 hours, and then vacuum dry it at 50°C for 24 hours to obtain a polymer composite membrane; immerse the polymer composite membrane in a secondary electrolyte dedicated to lithium-ion batteries to obtain a gel electrolyte membrane.

[0040] Example 2: The preparation method of the in-situ polymerized PMMA / TPU / HNT / 20% LALZO gel electrolyte membrane in this example is achieved by the following steps:

[0041] 1. Weighing:

[0042] Weigh the following materials respectively: methyl methacrylate (MMA) 6g, thermoplastic polyurethane (TPU) 4g, lithium hexafluorophosphate (LiPF6) 1g, N,N-dimethylformamide (DMF) 80g, azobisisobutyronitrile (AIBN) 0.3g, LALZO 2g, HNT 0.2g, PC 1g

[0043] 2. The operation process of preparing gel electrolyte is:

[0044] Step 1. Add methyl methacrylate (MMA) and thermoplastic polyurethane (TPU) to N,N-dimethylformamide (DMF) solvent, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add initiator azobisisobutyronitrile (AIBN), heat in a water bath at 55°C and magnetically stir at a speed of 500 r / min for 1 hour to obtain a mixed solution; add evenly mixed LALZO, HNT powder and PC to the mixed solution, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add lithium salt LiPF6, and magnetically stir at a speed of 500 r / min for 1 hour under room temperature and closed conditions to obtain a final mixed solution.

[0045] Step 2. Inject the mixed solution obtained in the previous step into a PTFE culture dish, place it in a forced air drying oven, and prepolymerize it at 70°C for 20 minutes; after prepolymerization, blow dry it at 60°C for 5 hours, and then vacuum dry it at 50°C for 24 hours to obtain a polymer composite membrane; immerse the polymer composite membrane in a secondary electrolyte dedicated to lithium-ion batteries to obtain a gel electrolyte membrane.

[0046] Example 3: The preparation method of in-situ polymerization PMMA / TPU / HNT / 30% LALZO gel electrolyte membrane is achieved by the following steps:

[0047] 1. Weighing:

[0048] Weigh the following materials respectively: methyl methacrylate (MMA) 6g, thermoplastic polyurethane (TPU) 4g, lithium hexafluorophosphate (LiPF6) 1g, N,N-dimethylformamide (DMF) 80g, azobisisobutyronitrile (AIBN) 0.3g, LALZO 3g, HNT 0.2g, PC 1g

[0049] 2. The operation process of preparing gel electrolyte is:

[0050] Step 1. Add methyl methacrylate (MMA) and thermoplastic polyurethane (TPU) to N,N-dimethylformamide (DMF) solvent, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add initiator azobisisobutyronitrile (AIBN), heat in a water bath at 55°C and magnetically stir at a speed of 500 r / min for 1 hour to obtain a mixed solution A; add evenly mixed LALZO, HNT powder and PC to the mixed solution A, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add lithium salt LiPF6, and magnetically stir at a speed of 500 r / min for 1 hour under room temperature and closed conditions to obtain a final mixed solution B.

[0051] Step 2. Inject the mixed solution B obtained in the previous step into a PTFE culture dish, place it in a forced air drying oven, and prepolymerize it at 70°C for 20 minutes; after prepolymerization, blow dry it at 60°C for 5 hours, and then vacuum dry it at 50°C for 24 hours to obtain a polymer composite membrane; immerse the polymer composite membrane in a secondary electrolyte dedicated to lithium-ion batteries to obtain a gel electrolyte membrane.

[0052] The PMMA / TPU / HNT / 30% LALZO gel electrolyte membrane obtained by the above preparation process was characterized.

[0053] ① The PMMA / TPU / HNT / 30% LALZO polymer composite membrane prepared in Example 3 without electrolyte absorption was characterized by SEM electron microscopy. The results are as follows: Figure 1As shown. Figure 1 It can be seen that the polymer composite matrix film that has not absorbed the electrolyte presents a highly porous and uniform continuous network structure. The polymer formed by the in-situ polymerization reaction runs through the continuous phase to obtain a polymer composite film with an interpenetrating network structure. LALZO and HNT are wrapped by PMMA / TPU and embedded in the interconnected network structure. Lithium ions can be more evenly transferred between the electrolyte interface and the negative electrode, which is conducive to the absorption of the electrolyte, thereby improving the ionic conductivity. Applying this structure to lithium batteries can inhibit the growth of lithium dendrites to a certain extent.

[0054] ② Conductivity test was performed on PMMA / TPU / HNT / LALZO (0-40%) gel electrolyte membranes with different LALZO contents prepared in Examples 1 to 5. The results are as follows: Figure 2 As shown by Figure 2 It can be seen that after adding LALZO, the ionic conductivity of the gel electrolyte membrane is significantly improved. This is because the transmission pathway of lithium ions is transformed from the amorphous region of PMMA / TPU polymer to the interface between PMMA / TPU / HNT / LALZO inorganic filler-polymer, which improves the ionic conductivity. With the increase of LALZO mass fraction, the ionic conductivity of the gel electrolyte membrane continues to increase. When the mass fraction is 30%, the ionic conductivity of the gel electrolyte membrane is as high as 6.75×10 -4 S / cm; however, when the LALZO mass fraction exceeds 30%, the ionic conductivity decreases significantly.

[0055] Example 4: The preparation method of the in-situ polymerized PMMA / TPU / HNT / 40% LALZO gel electrolyte membrane in this example is achieved by the following steps:

[0056] 1. Weighing:

[0057] Weigh the following materials respectively: methyl methacrylate (MMA) 6g, thermoplastic polyurethane (TPU) 4g, lithium hexafluorophosphate (LiPF6) 1g, N,N-dimethylformamide (DMF) 80g, azobisisobutyronitrile (AIBN) 0.3g, LALZO 4g, HNT 0.2g, PC 1g

[0058] 2. The operation process of preparing gel electrolyte is:

[0059] Step 1. Add methyl methacrylate (MMA) and thermoplastic polyurethane (TPU) to N,N-dimethylformamide (DMF) solvent, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add initiator azobisisobutyronitrile (AIBN), heat in a water bath at 55°C and magnetically stir at a speed of 500 r / min for 1 hour to obtain a mixed solution A; add evenly mixed LALZO, HNT powder and PC to the mixed solution A, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add lithium salt LiPF6, and magnetically stir at a speed of 500 r / min for 1 hour under room temperature and closed conditions to obtain a final mixed solution B.

[0060] Step 2. Inject the mixed solution B obtained in the previous step into a PTFE culture dish, place it in a forced air drying oven, and prepolymerize it at 70°C for 20 minutes; after prepolymerization, blow dry it at 60°C for 5 hours, and then vacuum dry it at 50°C for 24 hours to obtain a polymer composite membrane; immerse the polymer composite membrane in a secondary electrolyte dedicated to lithium-ion batteries to obtain a gel electrolyte membrane.

[0061] Example 5: The preparation method of the in-situ polymerized PMMA / TPU / HNT gel electrolyte membrane (without LALZO) in this example is achieved by the following steps:

[0062] 1. Weighing:

[0063] Weigh respectively: methyl methacrylate (MMA) 6g, thermoplastic polyurethane (TPU) 4g, lithium hexafluorophosphate (LiPF6) 1g, N,N-dimethylformamide (DMF) 80g, azobisisobutyronitrile (AIBN) 0.3g, HNT 0.2g, PC 1g

[0064] 2. The operation process of preparing gel electrolyte is:

[0065] Step 1. Add methyl methacrylate (MMA) and thermoplastic polyurethane (TPU) to N,N-dimethylformamide (DMF) solvent, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add initiator azobisisobutyronitrile (AIBN), heat in a water bath at 55°C and magnetically stir at a speed of 500 r / min for 1 hour to obtain a mixed solution A; add evenly mixed HNT powder and PC to the mixed solution A, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add lithium salt LiPF6, and magnetically stir at a speed of 500 r / min for 1 hour under room temperature and closed conditions to obtain a final mixed solution B.

[0066] Step 2. Inject the mixed solution B obtained in the previous step into a PTFE culture dish, place it in a forced air drying oven, and prepolymerize it at 70°C for 20 minutes; after prepolymerization, blow dry it at 60°C for 5 hours, and then vacuum dry it at 50°C for 24 hours to obtain a polymer composite membrane; immerse the polymer composite membrane in a secondary electrolyte dedicated to lithium-ion batteries to obtain a gel electrolyte membrane.

[0067] Example 6: The preparation method of the in-situ polymerized PMMA / TPU / HNT / 30% LALZO gel electrolyte membrane in this example is achieved by the following steps:

[0068] In this embodiment, the operation process of using BPO as an initiator to prepare PMMA / TPU / HNT / 30% LALZO is as follows:

[0069] 1. Weighing:

[0070] Weigh the following materials respectively: methyl methacrylate (MMA) 6g, thermoplastic polyurethane (TPU) 4g, lithium hexafluorophosphate (LiPF6) 1g, N,N-dimethylformamide (DMF) 80g, dibenzoyl peroxide (BPO) 0.3g, LALZO 3g, HNT 0.2g, PC 1g

[0071] 2. The operation process of preparing gel electrolyte is:

[0072] Step 1. Add methyl methacrylate (MMA) and thermoplastic polyurethane (TPU) to N,N-dimethylformamide (DMF) solvent, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add initiator azobisisobutyronitrile (AIBN), heat in a water bath at 55°C and magnetically stir at a speed of 500 r / min for 1 hour to obtain a mixed solution A; add evenly mixed HNT powder and PC to the mixed solution A, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add lithium salt, and magnetically stir at a speed of 500 r / min for 1 hour under room temperature and closed conditions to obtain a final mixed solution B.

[0073] Step 2. Inject the mixed solution B obtained in the previous step into a PTFE culture dish, place it in a forced air drying oven, and prepolymerize it at 70°C for 20 minutes; after prepolymerization, blow dry it at 60°C for 5 hours, and then vacuum dry it at 50°C for 24 hours to obtain a polymer composite membrane; immerse the polymer composite membrane in a secondary electrolyte dedicated to lithium-ion batteries to obtain a gel electrolyte membrane.

[0074] Example 7: The preparation method of the in-situ polymerized PMMA / TPU / HNT / 30% LALZO gel electrolyte membrane in this example is achieved by the following steps:

[0075] In this embodiment, the operation process of preparing PMMA / TPU / HNT / 30% LALZO using LiTFSI as lithium salt is as follows:

[0076] 1. Weighing:

[0077] Weigh the following materials respectively: methyl methacrylate (MMA) 6g, thermoplastic polyurethane (TPU) 4g, lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) 4g, N,N-dimethylformamide (DMF) 80g, azobisisobutyronitrile (AIBN) 0.3g, LALZO 3g, HNT 0.2g, PC 1g

[0078] 2. The operation process of preparing gel electrolyte is:

[0079] Step 1. Add methyl methacrylate (MMA) and thermoplastic polyurethane (TPU) to N,N-dimethylformamide (DMF) solvent, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add initiator azobisisobutyronitrile (AIBN), heat in a water bath at 55°C and magnetically stir at a speed of 500 r / min for 1 hour to obtain a mixed solution A; add evenly mixed HNT powder and PC to the mixed solution A, and magnetically stir at a speed of 500 r / min for 5 hours under room temperature and closed conditions, then add lithium salt LiTFSI, and magnetically stir at a speed of 500 r / min for 1 hour under room temperature and closed conditions to obtain a final mixed solution B.

[0080] Step 2. Inject the mixed solution B obtained in the previous step into a PTFE culture dish, place it in a forced air drying oven, and prepolymerize it at 70°C for 20 minutes; after prepolymerization, blow dry it at 60°C for 5 hours, and then vacuum dry it at 50°C for 24 hours to obtain a polymer composite membrane; immerse the polymer composite membrane in a secondary electrolyte dedicated to lithium-ion batteries to obtain a gel electrolyte membrane.

[0081] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing an in-situ polymerized PMMA / TPU-based dual-filler polymer gel electrolyte, characterized in that: The following steps are involved: Step 1, adding methyl methacrylate and thermoplastic polyurethane to a solvent, stirring under closed conditions until dissolved, then adding an initiator, continuing to stir and heating in a water bath under closed conditions for at least 1 hour, then adding aluminum-doped lithium lanthanum zirconium oxide (LALZO), nano-halloysite (HNT) and polycarbonate (PC) mixed evenly, stirring under closed conditions, then adding lithium salt, stirring under closed conditions until uniform, to obtain a mixed solution; Step 2, forming a film from the mixed solution obtained in step 1, prepolymerizing the film in the film-making process, then drying it by blowing air and then by vacuum drying, and then immersing it in an electrolyte to obtain a gel electrolyte; In step 1, the lithium salt is any one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate or lithium perchlorate; In step 1, the mass ratio of methyl methacrylate, thermoplastic polyurethane, LALZO, HNT, PC and lithium salt is 1: (0.5-1): (0.1-1): (0.01-0.05): (0.1-0.2): (0.1-0.2), and the amount of initiator used is 0.05%-0.1% of the mass of the polymerized monomer.

2. The preparation method according to claim 1, characterized in that: In step 1, the initiator is dibenzoyl peroxide or azobisisobutyronitrile.

3. The preparation method according to claim 1, characterized in that: In step 1, the solvent is one of N,N-dimethylformamide, N-methylpyrrolidone, tetrahydrofuran, and acetone, or a mixture of any ratio of any of them.

4. The preparation method according to claim 1, characterized in that: In step 1, the stirring is magnetic stirring, and the speed is controlled at 450r / min~600r / min.

5. The preparation method according to claim 1, characterized in that: In step 2, the temperature and time of prepolymerization are 60°C~70°C and 20min~30min respectively; the temperature and time of blast drying are 50°C~70°C and 5h~7h respectively; the temperature and time of vacuum drying are 50°C~60°C and 24h~28h respectively.

6. The preparation method according to claim 1, characterized in that: In step 2, the electrolyte is secondary electrolyte LB-008.

7. A gel electrolyte prepared by the method according to any one of claims 1 to 6.

8. Use of the gel electrolyte prepared by the method according to any one of claims 1 to 6 in a lithium metal battery.

Citation Information

Patent Citations

  • Preparation method of gel polymer electrolyte membrane

    CN103579674A

  • Preparation method of gel polymer lithium ion battery liquid absorption diaphragm

    CN111403813A